Blockade of the integrin αLβ2 but not of integrins α4 and/or β7 significantly prolongs intestinal allograft survival in mice. Issue 1 (1st July 2000) - Sarnacki, S; Auber, F; Crétolle, C; Camby, C; Cavazzana-Calvo, M; Müller, W; Wagner, N; Brousse, N; Révillon, Y; Fischer, A; Cerf-Bensussan, N
Abstract : BACKGROUND: Small bowel transplantation remains a difficult therapeutic option endangered by a high rate of rejection and infectious complications. To improve these clinical results, it is mandatory to set up animal models to test alternative immunosuppressive regimens which may lead to immunotolerance. AIMS: To determine the value of blockade of αLβ2 (LFA-1) and α4 and β7 integrins (α4β1, α4β7, and αEβ7) in the prevention of rejection of fetal small bowel grafts in mice and the effect of the association of calcineurin dependent drugs in anti-LFA-1 treated mice. METHODS: Adult recipient mice engrafted with allogeneic fetal small bowel received a short course of anti-α4 and/or anti-LFA-1 monoclonal antibodies (mAb) with or without FK506 or cyclosporin A. In addition, in a set of experiment, β7−/− mice were used as recipients. Graft biopsies were performed and processed for standard histology. RESULTS: Blockade of the pathways of the integrins α4 and β7 had a modest or no effect on intestinal graft survival. In contrast, transitory, short administration of anti-LFA-1 monoclonal antibody alone, when started before engraftment (day −1), allowed long term survival of intestinal grafts, even when associated with calcineurin dependent drugs. However, early withdrawal of FK506 reversed the immunosuppressive effect of anti-LFA-1 treatment. CONCLUSION: These results suggest that firstly, anti-LFA-1, but not anti-α4 mAb treatment, may be useful in improving the results of intestinal transplantation, and secondly, that this treatment is not incompatible with long term administration of tacrolimus currently used in the prevention of small bowel graft rejection in humans.